Growing up in public : coming of age in a digital world - Heitner, Devorah, 1975- (TarcherPerigee, an imprint of Penguin Random House LLC, 2023)
"The definitive book on helping kids navigate growing up in a world where nearly every moment of their lives can be shared and compared With social media and constant connection, the boundaries of privacy are stretched thin. Growing Up in Public shows parents how to help tweens and teens navigate boundaries, identity, privacy, and reputation in their digital world. We can track our kids' every move with apps, see their grades within minutes of being posted, and fixate on their digital footprint, anxious that a misstep could cause them to be "canceled" or even jeopardize their admission to college. And all of this adds pressure on kids who are coming of age immersed in social media platforms that emphasize "personal brand," "likes," and "gotcha" moments. How can they figure out who they really are with zero privacy and constant judgment? Devorah Heitner shows us that by focusing on character, not the threat of getting caught or exposed, we can support our kids to be authentically themselves. Drawing on her extensive work with parents and schools as well as hundreds of interviews with kids, parents, educators, clinicians, and scholars, Heitner offers strategies for parenting our kids in an always-connected world. With relatable stories and research-backed advice, Growing Up in Public empowers parents to cut through the overwhelm to connect with their kids, recognize how to support them, and help them figure out who they are when everyone is watching"--